EFFECT OF ADAPTIVE COOLING TECHNIQUE ON ENERGY USAGE PATTERNS OF A CENTRALIZED HVAC SYSTEM - TRI BHASKORO, PETRUS (2012)
Nowadays, due to world energy crisis and global warming, efforts to reduce energy consumption become doubled. One of the efforts is to find strategies for lower energy consumption by the centralized HVAC system since the system is a major energy consumer in many building. Field studies conducted by many researchers in many countries have found that adaptive comfort temperature (ACT) for naturally ventilated and air-conditioned building are higher than the recommended value. Previous works on this topic showed that using the ACT, around 20% of energy consumed by HVAC system could be saved without sacrificing people’s comfort. However, mechanical limitation of HVAC system, the effects of application of the indoor comfort temperatures on the HVAC system and its applicability for academic building has not been discussed in detail on previous research. Therefore, this work aims to develop adaptive cooling technique using ACT to reduce energy consumption of a centralized HVAC system in an academic building by taking into account design limitation, and effect of application of ACT on the HVAC system. The building model and its HVAC system were first built using a building simulation program (BPS), TRNSYS and validated by comparing the simulation results with experimental results. Adaptive cooling technique coupled with dual fan dual duct system was built as proposed technique for effective, efficient, and economical solution to reduce the energy consumption. The validated model was then used to analyze the performance of the HVAC system using current strategies and proposed technique. In case of academic bloc 16 in Universiti Teknologi PETRONAS, the results showed that the indoor comfort temperatures ranges during occupied and unoccupied periods were 24.29oC – 24.51oC and 28.04oC – 28.76oC, respectively, while the relative humidity was constant at 70%. The proposed technique is able to reduce the cooling load up to 28.54% and has payback period less than 5 years.